Assessing gut microbiota perturbations during the early phase of infectious diarrhea in Vietnamese children. (2nd January 2018) - The, Hao Chung; Florez de Sessions, Paola; Jie, Song; Pham Thanh, Duy; Thompson, Corinne N.; Nguyen Ngoc Minh, Chau; Chu, Collins Wenhan; Tran, Tuan-Anh; Thomson, Nicholas R.; Thwaites, Guy E.; Rabaa, Maia A.; Hibberd, Martin; et al.
ABSTRACT: Diarrheal diseases remain the second most common cause of mortality in young children in developing countries. Efforts have been made to explore the impact of diarrhea on bacterial communities in the human gut, but a thorough understanding has been impeded by inadequate resolution in bacterial identification and the examination of only few etiological agents. Here, by profiling an extended region of the 16S rRNA gene in the fecal microbiome, we aimed to elucidate the nature of gut microbiome perturbations during the early phase of infectious diarrhea caused by various etiological agents in Vietnamese children. Fecal samples from 145 diarrheal cases with a confirmed infectious etiology before antimicrobial therapy and 54 control subjects were analyzed. We found that the diarrheal fecal microbiota could be robustly categorized into 4 microbial configurations that either generally resembled or were highly divergent from a healthy state. Factors such as age, nutritional status, breastfeeding, and the etiology of the infection were significantly associated with these microbial community structures. We observed a consistent elevation of Fusobacterium mortiferum, Escherichia, and oral microorganisms in all diarrheal fecal microbiome configurations, proposing similar mechanistic interactions, even in the absence of global dysbiosis. We additionally found that Bifidobacterium pseudocatenulatum was significantly depleted during dysenteric diarrhea regardless of the etiological agent, suggesting that further investigations into the use of this species as a dysentery-orientated probiotic therapy are warranted. Our findings contribute to the understanding of the complex influence of infectious diarrhea on gut microbiome and identify new opportunities for therapeutic interventions.